An Improved Maturity Model for Electronic Court Case Management System from the Perspective of End Users in Malaysia - Adham M Alankar; Nurzi Juana Mohd Zaizi; Hanifah Abdul Hamid (Malaysian Journal of Science Health & Technology, 2026)
Many judicial systems are currently undergoing a significant digital transformation; however, there is no clear way to measure whether their Electronic Court Case Management Systems (ECCMS) are truly mature or not. In Malaysia, several nationwide court modernization programs have been underway. Since 2013, the end-user evaluation has remained somewhat fragmented. In this study, we propose an improved maturity model for an ECCMS and, after filtering out noisy and incomplete responses, test it on 300 active users from various Malaysian courts; 287 were used. The paradigm builds upon earlier e-government maturity models with four underlying constructs: second-order (1) human behaviour, (2) technological, (3) organisational factors, and (4) legal issues. Data were gathered using descriptive statistics, validity tests, and structural equation modelling (PLS-SEM), with a 5-point Likert scale. The structural model earned a Q²_predict value of 0.483 and an R² score of 0.8927, showing predictive power good but not perfect. Legal and regulatory aspects revealed, up to 0.713, the highest path coefficients, whereas technical and behavioural elements were marginally weaker. Although for further research there are still a few gaps, the accepted methodology provides a useful foundation for evaluating the development of e-justice. It can inform decisions about court digitalization, more data-driven.